The Positive Effect of Service Quality on Patient Satisfaction is Strengthened by the Implementation of Electronic Medical Records - Lisdiawati Lisdiawati; Rajindra Rajindra; Abdul Kadri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The implementation of Electronic Medical Records (EMR) in hospitals continues to face multiple challenges, including technical limitations, human resource readiness, and socio‑cultural factors that influence technology adoption. This study aims to analyze the direct effect of service quality on patient satisfaction and the moderating effect of EMR implementation in strengthening this relationship. A cross‑sectional design was applied with a total of 95 respondents. Data were collected using a structured questionnaire, and hypothesis testing was conducted using Structural Equation Modeling (SEM). The first-stage analysis (direct effect model) showed an R-square value of 0.55 and a path coefficient (β) of 0.740 with ρ (<0.001) ≤ 0.05, indicating a positive and significant effect of service quality on patient satisfaction. The second-stage analysis (moderating effect model) produced an R-square value of 0.47 and a path coefficient (β) of 0.271 with ρ (<0.003) ≤ 0.05, demonstrating that EMR implementation strengthens the influence of service quality on patient satisfaction. These findings highlight the strategic role of EMR in enhancing service effectiveness and improving patient satisfaction in hospital settings.Keywords: moderating effect; electronic medical records; service quality; patient satisfaction; hospital